2022
DOI: 10.3389/fmicb.2022.1019130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Bopu powder supplementation on intestinal development and microbiota in broiler chickens

Abstract: This study aimed to investigate the effect of dietary supplementation with Bopu powder on intestinal development and bacterial community composition in broiler chickens. A total of 486 1-day-old arbor acres broilers were fed a basal diet (CON group), a basal diet supplemented with 50 mg/kg aureomycin (AB group), or a basal diet supplemented with 40 mg/kg Bopu powder (BP group). The results showed that the BP group had significantly lower serum tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 59 publications
(77 reference statements)
4
7
0
Order By: Relevance
“…Villus height, crypt depth, and the V/C ratio are important parameters for the healthy gut of broilers and are directly related to the absorptive capacity of the mucosa [36]. A higher villus height and V/C ratio are better for the intestinal absorption of nutrients and for broiler growth [37]. In the present study, 1.25 GEBE significantly decreased the ratio of duodenal villus height to crypt depth, suggesting a negative effect of GEBE on intestinal health.…”
Section: Itemsupporting
confidence: 51%
“…Villus height, crypt depth, and the V/C ratio are important parameters for the healthy gut of broilers and are directly related to the absorptive capacity of the mucosa [36]. A higher villus height and V/C ratio are better for the intestinal absorption of nutrients and for broiler growth [37]. In the present study, 1.25 GEBE significantly decreased the ratio of duodenal villus height to crypt depth, suggesting a negative effect of GEBE on intestinal health.…”
Section: Itemsupporting
confidence: 51%
“…Bacteroides enhance the body’s immunity by interacting with the host immune system [ 59 ]. Colidextribacter contributes to regulating the inflammatory response and maintains the integrity of the gut mucosa [ 21 ]. This indicated that the dietary addition of 400 mg/kg Ile affects the composition of the intestinal flora and increases the abundance of beneficial bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Then, DNA concentration and purity were measured with 1% agarose gels, and DNA was diluted to 1 ng/μL using sterile water according to the measured concentration. The V3-V4 hypervariable regions of 16S rRNA were amplified using 515F-806R primer [ 21 ]. All PCR reactions were performed with 15 μL of Phusion ® High Fidelity PCR Master Mix (New England Biolabs, Ipswich, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of diamine oxidase (DAO) and D-lactate in the serum were measured using ELISA kits (Jiangsu Meimian Industrial Co., Ltd.) following a previous protocol ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to reports, dietary supplementation with IA improves the antioxidant capacity and promotes an increased abundance of advantageous microorganisms in the small intestine of laying hens ( 11 ). In addition, the dietary addition of 40 mg/kg Bopu powder with IA significantly affects intestinal development and function, as well as relieves intestinal inflammation and oxidative stress in broilers ( 12 ). However, it is still unclear whether the addition of Macleaya cordata IA to broiler diets can effectively mitigate the intestinal injury in broilers.…”
Section: Introductionmentioning
confidence: 99%